Pengaruh Bauran Promosi Terhadap Keputusan Pembelian Produk “Air-K” Pabrik AMDK K3PG Pasca Re-Branding - Inayati, Naila Nur (Jurnal Mahasiswa Manajemen, 2025)
Background – Re-branding is an effort made by a company to totally change or renew an existing brand to be better by not ignoring the company's initial goal of being profit-oriented. To provide information on products that have been re-branding, the company usually carries out promotions. The goal is to provide information to consumers, that the product has been changed brand by the company. Objective – The purpose of this study is to determine whether there is an influence of the promotional mix on the purchasing decision of K3PG bottled water products after making a brand change. Design / Methodology / Approach – This research is located at JL. Kayu Raya Perumahan Pongangan Indah, GKB and used 125 samples using accidental sampling. Data analysis uses multiple linear regression analysis. Findings – The results showed that advertising has no effect on product purchasing decisions, while personal selling, public relations, sales promotion, and direct marketing have a significant influence on purchasing decisions. Research Implication – The promotional mix applied consists of advertising, personal selling, sales promotion, public relations, and direct marketing. Of the five mixtures, advertising has a very big influence, because with advertising the company can persuade and influence consumers. Limitations – The variables used in this study are advertising, personal selling, public relations, sales promotion, and direct marketing on product purchasing decisions.